The facilitators’ point of view regarding the primary health care planning as a continuing education program - Kênia Lara Silva; Helen Cristiny Teodoro Couto Ribeiro; Lizziane D’ávila Pereira; Bárbara Ribeiro Martins; Juliana Alves Viana; Stephanie Marques Moura Franco Belga (Rev Rene)
This is a qualitative study that aims at analyzing the Primary Health Care Strategic Planning in a continuing education process, as well as the professional’s formation to work as facilitators in it. Data was obtained through interviews with 11 nurses that had acted as the plan’s facilitators in a municipality within Belo Horizonte. The results indicate that the experience as facilitators allowed them to reflect on the work process and this practice contributed to the incorporation of new tools to the primary health care system. The participants reported the difficulties faced when conducting the experience and the gap in the professionals’ formation to act in the PHC and to put into practice the processes of continuing education on a day to day basis. In conclusion, the Planning represents an important continuing education strategy and it is significance to transform processes and practices in the primary health care service.